Diet Supplemented With Synthetic Carotenoids: Effects on Growth Performance and Biochemical and Immunological Parameters of Yellow Perch (Perca flavescens) - Abd El-Gawad, Eman A.; Wang, Han-Ping; Yao, Hong (Frontiers in Physiology, 2019)
The current study assessed the effect of dietary canthaxanthin and lycopene supplementation at different concentrations on growth performance and antioxidant status in yellow perch (Perca flavescens). In this regard, fish with initial weight (32 ± 1.0 g) were divided into five groups in triplicate, and fed on carotenoid-free diet (control), canthaxanthin (CTX) (50 and 100 mg/kg diet), and lycopene (200 and 400 mg/kg diet) for 60 days. Growth parameters and antioxidant enzymes were evaluated after 30 and 60 days post feeding. Tissue liver and intestine from six fish per treatment was collected for antioxidant and digestive enzymes analysis. The results revealed a significant increase (P < 0.05) of lipid content in the group fed lycopene at a dietary level 400 mg/kg for 60 days, compared to the control. Moreover, dietary carotenoids exhibited no significant effect on growth performance; this was evidenced by no significant up-regulation of growth hormone (gh) and insulin-like growth factor 1b (igf-1b) genes after 30 and 60 days post feeding. Intestinal lipase and trypsin activities were significantly improved with dietary lycopene especially at a dose of (400 mg/kg diet) for 60 days. Malondialdehyde (MDA) level in liver was also significantly decreased with dietary lycopene (400 mg/kg diet) for 60 days. Hepatic superoxide dismutase (SOD), catalase (CAT), and Glutathione peroxidase (GSH-Px) activities were significantly decreased with dietary CTX, especially at dose (100 mg/ kg diet) and lycopene at a concentration of 200 and 400 mg/kg diet after 60 days feeding. Additionally, the immune-related gene interleukin-1 beta (il-1b) mRNA expression level revealed up-regulation in groups fed on CTX at different concentrations for 30 days, and fish fed lycopene at a concentration level 400 mg/kg diet for 60 days. The obtained results concluded that dietary supplementation of canthaxanthin and lycopene could enhance immune response and maintain antioxidants defense of fish. Therefore, it considered as a functional aquafeed ingredient for yellow perch.